1994
DOI: 10.1007/bf00023239
|View full text |Cite
|
Sign up to set email alerts
|

Differential accumulation of S-adenosylmethionine synthetase transcripts in response to salt stress

Abstract: NaCl stress causes the accumulation of several mRNAs in tomato seedlings. An upregulated cDNA clone, SAM1, was found to encode a S-adenosyl-L-methionine synthetase enzyme (AdoMet synthetase). Expression of the cDNA SAM1 in a yeast mutant lacking functional SAM genes resulted in high AdoMet synthetase activity and AdoMet accumulation. We show that tomato plants contain at least four SAM isogenes. Clones corresponding to isogenes SAM2 and SAM3 have also been isolated and sequenced. They encode predicted polypept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
1
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 54 publications
1
114
1
4
Order By: Relevance
“…The amount of this enzyme significantly decreased in the sample treated with moderate osmotic stress. A similar effect was also reported in other proteomic (Yan et al 2005;Toorchi et al 2009;Mohammadi et al 2012b) and transcriptomic (Espartero et al 1994) studies. This synthetase is probably involved in the control of gene expression under osmotic stress conditions due to its ability to methylate nucleic acids and, therefore, may constitute an interesting target for genetic engineering of plant resistance to this stress (Mohammadi et al 2012b).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The amount of this enzyme significantly decreased in the sample treated with moderate osmotic stress. A similar effect was also reported in other proteomic (Yan et al 2005;Toorchi et al 2009;Mohammadi et al 2012b) and transcriptomic (Espartero et al 1994) studies. This synthetase is probably involved in the control of gene expression under osmotic stress conditions due to its ability to methylate nucleic acids and, therefore, may constitute an interesting target for genetic engineering of plant resistance to this stress (Mohammadi et al 2012b).…”
Section: Discussionsupporting
confidence: 89%
“…Decrease in HSP70 expression in the triticale roots suggests, therefore, some disturbances in protein metabolism, perhaps caused by weak plant adaptation to stressful conditions. S-adenosylmethionine synthetase is an enzyme essential for DNA, RNA and protein methylation, biosynthesis of cell wall components and, indirectly, for the synthesis of polyamines and ethylene (Espartero et al 1994;Grillo and Colombatto 2008). It was revealed that the increased synthesis of polyamines (whose production depends on this synthase) increases tolerance of some plants to the osmotic stress (Wi et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…S-adenosyl-L-methionine serves as the major methyl-group donor, for example, in the synthesis of secondary products (Yang and Hoffman, 1984;Heby and Persson, 1990). Transcript 1465, which is identical to a second rice SAMS (Z29867), was not downregulated, indicating that SAMS isoforms are differentially regulated by salt stress, as has been seen for other species (Espartero et al, 1994;Schröder et al, 1997).…”
Section: The Time-specific Response Of Transcripts In Pokkalimentioning
confidence: 82%
“…Elevated mRNA levels for SAM synthetase and ethylene biosynthetic enzymes were apparent within 0.5 to 2 h after the onset of ozone exposure ( Figure 5). When RNA isolated from ozone-exposed tomato leaves was hybridized to genespecific SAM synthetase probes (Espartero et al, 1994), elevated transcript levels were detected for the main leaf isoform, SAM3, at 2 h ( Figure 5a). Transcript levels returned to the levels of control plants after 5 h. Induction of the SAM3 gene after 2 h of ozone exposure (200 nl 1-1) was also observed in the tomato cultivar Pearson when exposed under identical conditions ( Figure 5c): Transcript levels of SAM1 were not affected by ozone, and those of SAM2 were slightly reduced in treated as well as control plants under the experimental conditions used (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Ozone treatment induced expression of specific SAM and ethylene biosynthetic genes in the experimental plants. Increases at the mRNA level were specifically detected for only one out of three SAM synthetase genes, SAM3 (Espartero et aL, 1994), and one out of four ACC synthase genes, LE-ACS2 (Rottmann et aL, 1991;Yip et aL, 1992).…”
Section: Discussionmentioning
confidence: 97%